Analytical continuation of imaginary axis data for optical conductivity - Gunnarsson, Olle; Haverkort, Maurits W.; Sangiovanni, Giorgio (Physical review. B, Condensed matter and materials physics, 2010)
We compare different methods for performing analytical continuation of spectral data from the imaginary time or frequency axis to the real frequency axis for the optical conductivity σ(ω). We compare the maximum entropy (MaxEnt), singular value decomposition (SVD), sampling, and Padé methods for analytical continuation. We also study two direct methods for obtaining σ(0). For the MaxEnt approach we focus on a recent modification. The data are split up in batches, a separate MaxEnt calculation is done for each batch and the results are averaged. For the problems studied here, we find that typically the SVD, sampling, and modified MaxEnt methods give comparable accuracy while the Padé approximation is usually less reliable.